Shaking Table Tests on a New Antislide Pile under Earthquakes. (18th January 2021) - Lai, Jie; Liu, Yun; Wang, Wei
Abstract : A retaining form of a shock-absorbing antislide pile is proposed for slope engineering. A flexible material (shock-absorption layer) is filled in front of an ordinary antislide pile, which is used to absorb a large amount of seismic energy, thereby decreasing the transmission of seismic energy to the antislide pile. The flexible material thus reduces the seismic response, hence improving the aseismic capacity of the antislide pile. To verify the seismic performance of the shock-absorbing antislide pile, a shaking table contrast test was conducted and the results were compared with those from an ordinary antislide pile. The test results show that the flexible material absorbs a portion of the seismic deformation of the slip mass, decreasing the final displacement of the shock-absorbing antislide pile compared to that of the ordinary antislide pile, thereby reducing the sensitivity of the pile body to the displacement. Under the same conditions, the acceleration response of the slope body at the same height is lower for the shock-absorbing antislide pile than that for the ordinary pile, with the seismic performance of the former being superior to that of the latter. Furthermore, the shock-absorbing antislide pile is similar to the ordinary pile in terms of the dynamic earth pressure distribution form of the pile shaft; however, its value is relatively smaller, and the former exhibits better dynamic stress performance than the latter. The test results should prove useful for aseismic design of slopes.